2017
DOI: 10.22159/ijcpr.2017v9i2.17383
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Breast Cancer Classification Using Decision Tree Classifiers

Abstract: Breast cancer is one of the dangerous cancers among world's women above 35 y. The breast is made up of lobules that secrete milk and thin milk ducts to carry milk from lobules to the nipple. Breast cancer mostly occurs either in lobules or in milk ducts. The most common type of breast cancer is ductal carcinoma where it starts from ducts and spreads across the lobules and surrounding tissues. According to the medical survey, each year there are about 125.0 per 100,000 new cases of breast cancer are diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…However, in the non-basal-like type, a cytoplasmic p63 protein was lower than nuclear p63 protein. The p63 protein is a marker of squamous cell carcinoma at subcellular normal cells or hyperplastic ones appearing significantly in the epithelial cells and contributing to the increased invasion and aggressiveness of the tumor [26]. Specifically, the results of this research indicated that the sensitivity and specificity of cytoplasmic p63 protein in metaplastic breast cancer with basal-like type was 88.2%, while the sensitivity and specificity of nuclear p63 protein was 11.8%.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, in the non-basal-like type, a cytoplasmic p63 protein was lower than nuclear p63 protein. The p63 protein is a marker of squamous cell carcinoma at subcellular normal cells or hyperplastic ones appearing significantly in the epithelial cells and contributing to the increased invasion and aggressiveness of the tumor [26]. Specifically, the results of this research indicated that the sensitivity and specificity of cytoplasmic p63 protein in metaplastic breast cancer with basal-like type was 88.2%, while the sensitivity and specificity of nuclear p63 protein was 11.8%.…”
Section: Discussionmentioning
confidence: 75%
“…The basal-like and TNBC were associated [23]. In addition, the expression of p63 protein derived from basal epithelial cells is strongly influenced by the intensity of tumor cell development such as cell nutrition factor [24], chemotherapy, regulation, and p63 protein synthesis [25] both in nucleus and cytoplasm [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the computer aided diagnosis demands an enhancement in mammographic images there by increasing the efficiency in detection based on advanced image processing and pattern recognition techniques. P. Hamsagayathri, P. Sampath [5],proposed a work to analyzes the different decision tree classifier algorithms for Wisconsin original, diagnostic and prognostic dataset using WEKA software. The performance of the classifiers are evaluated against the parameters like accuracy, Kappa statistic, Entropy, RMSE, TP Rate, FP Rate, Precision, Recall, F-Measure, ROC, Specificity, Sensitivity.…”
Section: Related Workmentioning
confidence: 99%
“…Random Trees have been introduced by Leo Breiman and Adele Cutler. This algorithm can deal with both classification and regression problems [21,35]. The structure for a Random Tree is shown in Fig.…”
Section: Random Treementioning
confidence: 99%